Association Between Degrees of Separation in Physician Networks and Surgeons' Use of Perioperative Breast Magnetic Resonance Imaging. Issue 6 (June 2019) - Shi, Yongren; Pollack, Craig E.; Soulos, Pamela R.; Herrin, Jeph; Christakis, Nicholas A.; Xu, Xiao; Gross, Cary P.
Abstract : Background: Perioperative magnetic resonance imaging (MRI) is frequently used in breast cancer despite unproven benefits. It is unclear whether surgeons' use of breast MRI is associated with the practices of other surgeons to whom they are connected through shared patients. Methods: We conducted a retrospective study using Medicare data to identify physicians providing breast cancer care during 2007–2009 and grouped them into patient-sharing networks. Physician pairs were classified according to their "degree of separation" based on patient-sharing (eg, physician pairs that care for the same patients were separated by 1 degree; pairs that both share patients with another physician but not with each other were separated by 2 degrees). We assessed the association between the MRI use of a surgeon and the practice patterns of surgical colleagues by comparing MRI use in the observed networks with networks with randomly shuffled rates of MRI utilization. Results: Of the 15, 273 patients who underwent surgery during the study period, 28.8% received perioperative MRI. These patients received care from 1806 surgeons in 60 patient-sharing networks; 55.1% of surgeons used MRI. A surgeon was 24.5% more likely to use MRI if they were directly connected to a surgeon who used MRI. This effect decreased to 16.3% for pairs of surgeons separated by 2 degrees, and 0.8% at the third degree of separation. Conclusions: Surgeons' use of perioperative breast MRI is associated with the practice of surgeons connected to them through patient-sharing; the strength of this association attenuates as the degree of separation increases. Abstract : Supplemental Digital Content is available in the text.